The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1073/pnas.81.19.6169
|View full text |Cite
|
Sign up to set email alerts
|

Development of encephalopathic features similar to Reye syndrome in rabbits.

Abstract: The progression of neurological abnormalities through four or five clinically distinguishable levels of deepening coma and the development of a fatty liver are the hallmarks of Reye syndrome. A number of animal models have been described that result in fatty liver formation with minimal, static, or catastrophic neurological changes. In this study, we attempted to produce neurological features in rabbits that reflected a rostral-caudal progression of abnormalities that could be categorized into clinically disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1986
1986
1995
1995

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…There were several notable differences in RBC phospholipid fatty acids between RS patients (nos. [8][9][10][11][12][13][14] and ICU controls during the first 48 h of hospital admission. In …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were several notable differences in RBC phospholipid fatty acids between RS patients (nos. [8][9][10][11][12][13][14] and ICU controls during the first 48 h of hospital admission. In …”
Section: Resultsmentioning
confidence: 99%
“…In vitro and in vivo experiments in animals have demonstrated that polyunsaturated fatty acids can cause cerebral edema ( 6 4 , a cardinal clinical feature of RS. In a rabbit model of RS, Kang et al (9) have shown that intracisternal injection of free PUFA leads to a reproducible dose-titratable encephalopathy; they and others have proposed that PUFA may be acting as toxins in RS. There have been no attempts to measure the lipid profile of any tissue during acute RS. Since the majority of PUFA in the cells is in phospholipids, we believe tissue lipid analysis could add to the understanding of the role of PUFA in this syndrome.…”
mentioning
confidence: 99%
“…Pathological changes in the brain and liver and a poor neurological outcome are correlated with elevations in levels of serum fatty acids and ammonia (DeLong and Glick, 1982;Heubi et al, 1984;Dezateux et al, 1986). In animal models, administration of octanoic acid, other short-to medium-chain-length fatty acids, or polyunsaturated fatty acids can mimic the neuropathological changes of Reye's syndrome (Glasgow and Chase, 1975;Trauner, 1982;Kang et al, 1984).…”
mentioning
confidence: 99%